Fat mass and obesity-related (FTO) shuttles between the nucleus and cytoplasm. Issue 5 (22nd October 2014) - Gulati, Pawan; Avezov, Edward; Ma, Marcella; Antrobus, Robin; Lehner, Paul; O'Rahilly, Stephen; Yeo, Giles S. H.
Abstract : Exportin interacts with FTO and this interaction might be involved in the nucelocytoplasmic shuttling of FTO in the cell. Abstract : SNPs (single nucleotide polymorphisms) on a chromosome 16 locus encompassing FTO, as well as IRX3, 5, 6, FTM and FTL are robustly associated with human obesity. FTO catalyses the Fe(II)- and 2OG-dependent demethylation of RNA and is an AA (amino acid) sensor that couples AA levels to mTORC1 (mammalian target of rapamycin complex 1) signalling, thereby playing a key role in regulating growth and translation. However, the cellular compartment in which FTO primarily resides to perform its biochemical role is unclear. Here, we undertake live cell imaging of GFP (green fluorescent protein)-FTO, and demonstrate that FTO resides in both the nucleus and cytoplasm. We show using 'FLIP' (fluorescence loss in photobleaching) that a mobile FTO fraction shuttles between both compartments. We performed a proteomic study and identified XPO2 (Exportin 2), one of a family of proteins that mediates the shuttling of proteins between the nucleus and the cytoplasm, as a binding partner of FTO. Finally, using deletion studies, we show that the N-terminus of FTO is required for its ability to shuttle between the nucleus and cytoplasm. In conclusion, FTO is present in both the nucleus and cytoplasm, with a mobile fraction that shuttles between both cellular compartments, possibly by interaction with XPO2.